Effect of EM propagation medium on electrorheological characteristics of dielectric nanofluids - Adil, M. (Taylor and Francis Inc., 2017)
The effect of dielectric loss on the electrorheological (ER) characteristic of dielectric nanofluids under shear was studied. When nanofluids are activated by an applied electric field, it behaves like a non-Newtonian fluid under ER effect by creating the chains of nanoparticles. ER characteristics of ZnO and Al2O3 nanofluids with various nanoparticles concentration (0.1, 0.05, 0.01 wt) were measured. For this purpose, a solenoid-based electromagnetic (EM) transmitter was used under different propagation media including air, tap water, and salt water. The result shows that all the nanofluids exhibit pseudo-plastic behavior, while the electric field causes a significant increase in viscosity in the presence of tap water, followed by salt water. Additionally, the viscosity of nanofluid shows a high dependence on particle loading. A possible mechanism was also proposed to describe the effect of dielectric properties on the ER behavior of dielectric nanofluids. © 2017, Copyright © Taylor & Francis Group, LLC.